2021
DOI: 10.1111/jocd.14521
|View full text |Cite
|
Sign up to set email alerts
|

Can SARS‐CoV‐2 vaccine increase the risk of reactivation of Varicella zoster? A systematic review

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 31 publications
2
29
0
5
Order By: Relevance
“…Recently, COVID-19 vaccination was reported as a triggering factor of HZ. 8 Iwanaga et al 9 reported 399 cases of HZ after receiving the vaccine of COVID-19. There might be a link between COVID-19 vaccine and HZ emergence; however, the mechanism is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, COVID-19 vaccination was reported as a triggering factor of HZ. 8 Iwanaga et al 9 reported 399 cases of HZ after receiving the vaccine of COVID-19. There might be a link between COVID-19 vaccine and HZ emergence; however, the mechanism is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Similarly, HZ was detected in cases of COVID vaccination within first week to the fourth week of vaccination with mean period between HZ and COVID-19 vaccination was 7.64 days. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las vacunas disponibles en nuestro país son BBIPB – Corv (Sinopharm), BNT162b2 (Pfizer-BioNTech) y ChAdOx1-S (AstraZeneca) 3 . Aunque todavía, se desconocen los posibles efectos adversos a largo plazo de esta nueva generación de vacunas, los efectos secundarios comunes relacionados con la vacunación incluyen el dolor, enrojecimiento y/o hinchazón en el lugar de la inyección, fatiga, cefalea, fiebre y escalofríos 4 . (See Tabla 1 .)…”
Section: Introductionunclassified
“…Los efectos adversos más comunes a las vacunas son dolor en el sitio de inyección, fiebre, dolor de cabeza, náuseas y vómitos 4 . La aparición de herpes zóster después de la administración de alguna vacuna es un hallazgo que no es frecuente hallar en la literatura 1 , pero se han descrito casos de herpes zóster tras la vacunación de vacunas inactivadas contra la influenza, hepatitis A, rabia y encefalitis japonesa 7 .…”
Section: Introductionunclassified